Who discusses reaching a healthy weight with a general practitioner? Findings from the 2014–15 Australian National Health Survey. Issue 5 (September 2018) - Kilpatrick, Michelle; Nelson, Mark; Palmer, Andrew; Jose, Kim; Venn, Alison
Abstract: Objective: General practitioners (GPs) can positively impact upon patient intentions to lose weight and weight management, and are important in the referral pathway to specialist weight-loss programs and surgical interventions. The aim of this study was to investigate the characteristics and proportions of Australians who report talking to a GP about weight management. Methods: Cross-sectional data from 15, 329 participants aged 15 years and over in the 2014–15 Australian National Health Survey were used. Proportions (with 95% confidence intervals (95%CI)) of respondents who reported discussing reaching a healthy weight with a GP in the previous 12 months were estimated, categorised by demographic, social and health characteristics. Results: We found that 10.8% (95%CI:9.8–11.8) of overweight participants, 24.4% (95%CI:22.7–26.4) with Class 1 obesity (30 ≤ BMI < 35 kg/m 2 ) and 41.8% (95%CI:38.3–45.3) with Classes II/III obesity (BMI ≥ 35 kg/m 2 ) reported discussing weight with a GP. Higher proportions of respondents with Class II/Class III obesity and poor/fair self-reported health (50.2%, 95%CI:43.3–57.0), or high/very high levels of psychological distress (53.3%, 95%CI:43.7–61.4), or diabetes (64.8%, 95%CI:51.9–77.3) reported discussing weight. As age, number of GP visits, or comorbid conditions increased, the proportions of people who discussed their weight with a GP also increased, across all weight classes. Conclusions: While discussions are more likely with increasing BMI and comorbidities, most Australians with overweight and obesity appear to be missing opportunities to discuss reaching a healthy weight with their GP. Policies, training and education programs to encourage this dialogue could lead to earlier and more beneficial weight-related interventions.